Fraud Prevention in the Perspective of Internal Audit, Internal Control, Whistleblowing System, and Professional Ethics in Palm Oil Company - Burahman, Habi; Ahmar, Nurmala; Syam, Ardiansyah; Lysandra, Shanti; Djaddang, Syahril (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The study aims to analyze the impact of internal audit, internal control and whistleblowing system on fraud prevention with professional ethics moderation. Research is a quantitative study using primary data collected using a questionnaire forming a list of written questions about issues to be discussed to respondents. A total of 325 respondents answered the questionnaire thoroughly and analyzed. Testing the moderated regression analysis hypothesis. The results show that internal audits, internal controls and whistleblowing system have a significant impact on fraud prevention. Professional ethics are able to moderate the variable of internal control in fraud prevention. Specifically, the samples came from a palm oil company that has unique characteristics in determining fraud prevention strategies. The next researcher could develop it by adding decision-making variables in fraud prevention to similar industries or other industries.